2017
DOI: 10.1007/s00701-017-3237-6
|View full text |Cite
|
Sign up to set email alerts
|

Shunt age-related complications in adult patients with suspected shunt dysfunction. A recommended diagnostic workup

Abstract: Symptoms of SD remain mostly unspecific. This study showed that the type of SD depends on the time interval from implantation. We propose a workup strategy for patients with SD based on the temporal profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…The predominant symptoms of shunt dysfunction are headache, nausea, vomiting, gait disturbances, visual alterations, neuropsychological deficits, and urinal incontinence [ 6 ]. The risk of shunt dysfunction according to the international literature is from 30% to 50% after 3 years follow-up [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The predominant symptoms of shunt dysfunction are headache, nausea, vomiting, gait disturbances, visual alterations, neuropsychological deficits, and urinal incontinence [ 6 ]. The risk of shunt dysfunction according to the international literature is from 30% to 50% after 3 years follow-up [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The risk of shunt dysfunction according to the international literature is from 30% to 50% after 3 years follow-up [ 4 ]. The clinical presentation of our patient led us to suspect a new shunt dysfunction and according to the study protocol reported in the international literature we realized a CT scan and LP to find the etiology [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…infection, but overdrainage and mechanical failure continue to pose problems. The diagnosis of shunt malfunction based on a careful clinical history, examination, and investigations such as computed tomography (CT) scanning and plain X-ray shunt series, is not always straightforward [45]. For example, ventricular size may not change in cases with a blocked shunt.…”
Section: This Article Is Part Of the Topical Collection On Csf Circulmentioning
confidence: 99%
“…Classical symptoms of shunt malfunction are nonspecific and include headache, lethargy, nausea, and vomiting. [27] When patients present to the ER with symptoms of shunt failure, workup of shunt failure typically begins with brain imaging (computed tomography [CT] scans and shunt X-rays). Unfortunately, shunt failures do not necessarily lead to imaging changes, and hydrocephalus itself does not always indicate shunt failure.…”
Section: Introductionmentioning
confidence: 99%